The Paradigm Of The Word Hanif In The Qur'an: A Study Of Mawdu'i Tafsir - Sihabudin, Sihabudin; Hadani, Abdullah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
Mawdu’i commentary is a method of Quranic interpretation that analyzes a specific surah or gathers verses with similar themes under one topic. This study employs a mawdu’i approach to examine the meaning of hanif in the Qur’an, focusing on verses that explicitly contain the word without including its derivations. The objective is to determine the criteria of the hanif religion practiced by Prophet Ibrahim while comparing interpretations from Meccan and Medinan period verses. Additionally, this research explores scholarly perspectives to contextualize the concept of hanif in Islamic theology. Using a qualitative mawdu’i approach, this study integrates linguistic, theological, and historical analyses. Its novelty lies in the contextual comparison of Quranic revelations, offering a dynamic interpretation of hanif. The findings reveal five key characteristics of the hanif religion: an inclination toward monotheism, sincerity in worship, belief in all messengers of Allah, orientation toward the Kaaba and Hajj, and a strong commitment to affirming Allah’s Oneness. This research highlights the Quranic legitimacy of Islam as the continuation of Ibrahim’s millah, distinguishing it from Jewish and Christian claims. By providing a structured thematic analysis, this study enhances the understanding of hanif and its relevance in contemporary Islamic thought. It emphasizes hanif as a foundational principle of monotheism, guiding Muslims in faith and devotion to Allah.